1996
DOI: 10.1111/j.2044-8279.1996.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning disabled and average readers' working memory and comprehension: does metacognition play a role?

Abstract: The present study investigates (a) whether learning disabled readers' working memory deficits that underlie poor reading comprehension are related to a general system, and (b) whether metacognition contributes to comprehension beyond what is predicted by working memory and word knowledge. To this end, performance between learning and disabled (N = 60) and average readers (N = 60) was compared on the reading comprehension, reading rate, and vocabulary subtests of the Nelson Skills Reading Test, Sentence Span te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 28 publications
3
17
0
3
Order By: Relevance
“…poor decoders, students suffering from dyslexia, or other learning-disabled students; cf. Gersten, Fuchs, Williams, & Baker, 2001;Swanson & Trahan, 1996). The present study pertained to students who were proficient readers, while varying in metacognitive skillfulness during text studying.…”
Section: Intellectual Ability and Metacognitive Skills In Novice Learmentioning
confidence: 97%
“…poor decoders, students suffering from dyslexia, or other learning-disabled students; cf. Gersten, Fuchs, Williams, & Baker, 2001;Swanson & Trahan, 1996). The present study pertained to students who were proficient readers, while varying in metacognitive skillfulness during text studying.…”
Section: Intellectual Ability and Metacognitive Skills In Novice Learmentioning
confidence: 97%
“…Swanson and Trahan (1996) found that both working memory and comprehension were deficient in learning-disabled readers. If task knowledge is not already possessed by the learner, more resources will have to be allocated during task performance to figuring out the lower-order skills (such as decoding, computation, letter formation) rather than focusing on the higher-order aspects of the task such as comprehension or generation of creative ideas.…”
Section: In Academic Tasksmentioning
confidence: 98%
“…For example, Winograd and Paris (1989) found that SLDdiagnosed children were unable to solve problems they encountered while reading, nor did they have plans or strategies for making sense of the text being read. It was found that the metacognitive reading awareness of students with reading disability was lower than that of their TD peers (Chapman & Tunmer, 1997;Swanson & Trahan, 1996), while students with difficulty in reading had inadequate metacognitive reading skills, as well as skills for organizing the understanding of a text and establishing a connection between the text and the meaning (Botsas & Padeliadu, 2004). In a study by Baydık (2011), it was reported that students with difficulty in reading did not use different strategies in order to better understand the text; they also had lower levels of strategy usage in comparison to their peers.…”
Section: Discussionmentioning
confidence: 99%